Sequential left internal mammary artery grafting in combination with the aortic no-touch technique - Bulut, Ali; İnce, İlker; Sungur, Ümit; Kurtoğlu, Murat; Kızıltepe, Uğursay (Kardiochirurgia i torakochirurgia polska, 2022)
Introduction This study aimed to investigate the short-term outcomes achieved with off-pump bypass combined with the aortic no-touch technique where sequential anastomoses between the left internal mammary artery (LIMA), left anterior descending (LAD) and diagonal artery were employed. Material and methods A total of 583 patients (mean age 63, 80% male) who underwent off-pump bypass (LIMA-diagonal-LAD sequential) were enrolled in this retrospective analysis. Data regarding the frequency of in-hospital postoperative complications, intra-aortic balloon pump (IABP) and inotropic agent requirement, re-exploration for bleeding, and length of hospital stay were collected. Anastomosis patency was evaluated in 49 patients who underwent angiography. Results 2.6% of the participants received inotropic agents and 0.5% required IABP. Frequency of acute renal failure, sternal wound infection, cerebrovascular event, respiratory failure, and hemodialysis was less than 1% in total. Among the 49 patients undergoing angiography at an average 41 ±17 months after bypass, the LIMA-LAD was patent in 98% and the LIMA-diagonal was patent in 84% of the subjects. Preoperative left ventricle ejection fraction (LVEF) and recent myocardial infarction (MI) prior to bypass were significantly correlated with postoperative IABP and inotropic agent requirement (r = 0.165, p < 0.01 for LVEF, p = 0.021 for recent MI). Conclusions Off-pump bypass in combination with the aortic no-touch technique is associated with favorable postoperative outcomes including reduced postoperative stroke, renal dysfunction, IABP, and inotropic agent requirement compared to the results of previous randomized prospective studies published in the literature.